THE ALGORITHMIC APPROACH TO IMPROVEMENT OF WORK GENETIC ALGORITHM IN THE HOMOGENEOUS MINIMAX PROBLEM - Valery G. KOBAK; Dmitry V. TITOV; Valery V. KOBAK (Advanced Engineering Research)
The given work states an estimation to two updatings of genetic algorithm which give decisions very close to optimum, for polynom time. Both these of algorithm, lead, finally, to the decision of a two-instrument minimax problem, however on various computing ways.